The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1021/acs.macromol.3c02353
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nucleation in Stereodefective Isotactic Polypropylene: The Impact of Stereodefects on the Melt Memory

Alessandra Cicolella,
Fabio De Stefano,
Miriam Scoti
et al.

Abstract: The memory of crystals in the melt of stereodefective samples of isotactic polypropylene (iPP), characterized by different concentrations of rr stereodefects from 0.49 to 10.5 mol %, was analyzed. Experiments of self-nucleation and annealing have demonstrated that high contents of rr stereodefects, largely incorporated in the crystals of iPP, produce a significant memory of crystals in the melt that persists up to high temperatures well above the melting temperature. For low stereodefect concentrations (lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In addition, De Rosa et al reported a remarkable melt memory in propene–pentene isotactic copolymers 21 and stereodefective iPP. 35 Their results indicated that the melt memory effect of iPP, which persists in the melt up to high temperatures, is evident not only in copolymers with non-crystallizable comonomers, but also in those with small defects largely included in the crystals. Recently, the melt memory effect above T 0 m in rigid poly(arylene ether sulfone ketone) homopolymers has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, De Rosa et al reported a remarkable melt memory in propene–pentene isotactic copolymers 21 and stereodefective iPP. 35 Their results indicated that the melt memory effect of iPP, which persists in the melt up to high temperatures, is evident not only in copolymers with non-crystallizable comonomers, but also in those with small defects largely included in the crystals. Recently, the melt memory effect above T 0 m in rigid poly(arylene ether sulfone ketone) homopolymers has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the thermal stability of the condensed structures in polymers extends beyond the crystal melting point and resists the formation of other possible structures associated with original crystallization. , The crystallization of polymers depends on the thermal properties. The residual structures retained in the molten state owing to the memory effect influence subsequent recrystallization, accelerating the kinetics of crystallization. , Thus, the underlying mechanism governing the memory effect of the condensed structures of polymers should be studied for controlling the morphology and properties of the final crystallites.…”
Section: Introductionmentioning
confidence: 99%